The St. Nicholas anthology - Commager, Henry Steele, 1902-1998.; American Council of Learned Societies (New York : Greenwich House : Distributed by Crown Publishers, 1983)
Contains the "best" of "St. Nicholas," a magazine for boys and girls published at the turn of the 20th century. Included stories, poems, an d original illustrations.
In the twilight / Eudora Welty -- Mystery / Stephen Vincent Benet -- Frozen brook / Stella Benson -- Home, to Penelope / Bruce T. Simonds - - Vacation song / E. Vincent Millay -- Voice of the city / John C. Farr ar -- Vacation down south / E. Babette Deutsch -- Gratitude / Cornelia Otis Skinner -- In June-time / William R. Benet -- When swallows build / Corey H. Ford -- Where do the fairies meet? / Jessica Nelson North -- Winter walk / Rachel Lyman Field -- Song of summer / Sterling North -- Song of the woods / Stephen Vincent Benet -- My favorite character in fiction / Anne L. Parrish -- Four charades / C.P. Cranch -- Eight chara des, done up in rhyme, for lad and lass at candle-time / Ralph Henry Ba rbour -- Cross-word enigma / G.F. Babcock -- Anagram -- Double-acrostic / Elinor Lothrop Daniels -- Connected squares / Florence and Edna -- D iamond / Jennie N. Child -- Illustrated primal acrostic -- "Aged" puzzl e / Helen A. Sibley -- Oblique rectangle / George Linwood Hosea -- Magi c letters / Maurice P. Dunlap -- M.M.D. / Josephien Daskam Bacon.
Originally published: New York : Random House, 1948-1950.
Electronic text and image data.
Keywords: Children's literature; Literature -- Collections; Short stories